Impact of factor quality improvement on agricultural carbon emissions: Evidence from China’s high-standard farmland - Yang, Ningze; Sun, Xuetao; Qi, Qi (Frontiers in Environmental Science, 2022)
Reducing agricultural carbon emissions is essential to address climate change comprehensively, and improving factor quality reduces agricultural carbon emissions by promoting agricultural transformation. Based on the policy experiment of high standard farmland construction in China, this paper analyzes the role of factor quality in reducing agricultural carbon emissions using the SARAR model and data from 280 urban agricultural sectors. The study finds a significant spatial correlation between agricultural carbon emissions and factor quality improvement. Factor quality improvement can reduce agricultural carbon emissions. The disequilibrium effect analysis finds that the impact of factor quality improvement on agricultural carbon emissions has a disequilibrium effect. In other words, factor quality improvement mainly affects agricultural carbon emissions in areas with a higher level of agricultural development. The mediating test suggests that factor quality reduces improvement of agricultural carbon emissions and promotes the transformation of agricultural industrial structure through the mediating factor of agricultural carbon emissions. Finally, in addressing global climate change, this paper attempts to provide policy references for developing countries to reduce agricultural carbon emissions from factor quality improvement.